PENGARUH SUHU PASTEURISASI TERHADAP PROFIL DAN AKTIVITAS ANTIOKSIDAN PUREE BUAH NAGA MERAH - Sugiyanto, Maya Kumalasari; Sumual, Maria F.; Djarkasi, Gregoria S. S. (Jurnal Teknologi Pertanian (Agricultural Technology Journal, 2020)
AbstractAntioxidants can inhibit oxidative stress. Red dragon fruit (Hylocereus polyrhizus) is a source of plant containing antioxidant flavonoids. The processing of red dragon fruit into puree can maintain the nutritional value and taste of the fruit. The purpose of this study was to identify the antioxidant profile and antioxidant activity of red dragon fruit puree (Hylocereus polyrhizus) which was produced through the pasteurization process at temperatures of 65oC, 75oC, 85oC.The method used in this research is the experimental method. The parameters measured were the analysis of bioactive compounds which included total phenols, flavonoids, anthocyanins, antioxidant activity using the DPPH and FRAP methods, water content and crude fiber content. The results obtained in this study were total phenol at 65oC 1,15 mg GAE /g, 75oC 0,94 mg GAE /g, 85oC 0,91 mg GAE /g, 95oC 0,84 mg GAE /g, levels of flavonoids in 65oC treatment 0,71 mg QE /g, 75oC 0,70 mg QE /g, 85oC 0,70 mg QE /g, 95oC 0,56 mg QE /g, anthocyanin levels at 65oC 51,18%, 75oC 38,13%, 85oC 37,96%, 95oC 29,55%, IC50 value for antioxidant activity of DPPH method at 65oC 4,18 mg /ml, 75oC 107,74 mg /ml, 85oC 109,22 mg /ml, 95oC 112,56 mg /ml, the antioxidant activity of the FRAP method at 65oC 12,75 mg, 75oC 12,45 mg, 85oC 11,24 mg, 95oC 9,90 mg, water content at 65oC 88,66%, 75oC 89,13%, 85oC 89,06%, 95oC 83,8% and crude fiber content at temperature 65oC 7,7%, 75oC 7,06%, 85oC 7,39%, 95oC 6,52%.The conclusion of this study is that higher pasteurization temperature treatment can reduce the content of bioactive compounds and antioxidant activity in red dragon fruit puree.Keywords: Red Dragon Fruit Puree, Antioxidant Profile, Antioxidant Activity